RHD Genotypes in a Chinese Cohort of Pregnant Women - Zhang, Jianjun; Zeng, Yan; Wang, Yuefeng; Fan, Jiaming; Chen, Haijiang; Yang, Dan; Shi, Xiaoliang; Xu, Hualin; Fu, Zimu; Sheng, Fang; Xuan, Jie; Pan, Xiaoxi; et al. (Frontiers in Genetics, 2021)
RHD variants in D¯ Chinese pregnant women arose difficulties in management during pregnancy. Therefore, this study aims to precisely manage D¯ pregnant women by evaluating the spectrum of RHD mutations in D¯ pregnant women and getting insight into the rare alleles of RHD. A total of 76 D¯pregnant women were analyzed by performing polymerase chain reactions with sequence-specific primers (PCR-SSP), the 10 RHD exon Sanger sequencing, RHD zygosity detection, and mRNA sequencing (mRNA-seq). About 40% of alleles are variations of RHD, including  RHD 1227A homozygous, RHD-CE(2-9)-D, et al. Therefore, we established a molecular diagnostic strategy for Chinese women, and most D¯ pregnant women can be diagnosed with this simple decision tree. After RHD genotyping for D¯ pregnancy women, we eliminate at least 15% unnecessary ante- and postpartum injections of RhIG. As the first pedigree study and the first functional analysis under physiological conditions, mRNA-seq revealed that c.336-1G>A mutation mainly led to the inclusion of the intron 2, and exon 3 skipping, which indirectly explained the D¯ phenotype in this family. We also developed a robust protocol for determining fetal RhD status from maternal plasma. All 31 fetuses were predicted as RhD positive and confirmed the RhD status after birth.